Erythrocyte glutathione peroxidase activity analysis: manual colourimetric method versus commercial ELISA kit - Alsharif, A. H. K. H.; Hamzah, Hazilawati; Shaari, Mohd Rosly; Mohamed Mustapha, Noordin; Sithambaram, Shanmugavelu; Haron, Abd Wahid; K., Musaddim; A. M., Nabil (2012)
This study was conducted to determine erythrocyte glutathione peroxidase (GSH-Px) activity, in pregnant Boer does supplemented daily with and without dried Morinda citrifolia fruit, analysed using two different methods; a manual colourimetric method (direct method) and a commercial GSH-Px ELISA kit. The does were supplemented with M. citrifolia fruit started from third trimester of pregnancy until 2.5 months post partum. Results showed that GSH-Px analysed using the direct method produced insignificant differences between the groups throughout the experimental period, while the commercial ELISA kit produced some significant differences between the groups during the experiment. These indicate that erythrocyte GSH-Px activity is more stable analysed using the commercial kit and hence provides more accurate results compared to the direct method.